After universalisms: music as a medium for intercultural translation - Viljoen, Martina (Acta Academica: Critical views on society, culture and politics, 2012)
Postmodernity is characterised by the fundamentalisation of plurality. As Aleida Assmann (1996: 99) finds, difference is affirmed in the form of deviance, gaps, and radical alterity. Within this intellectual milieu, the acknowledgment of alterity and the acceptance of difference have become foremost ethical claims (Assmann 1996: 99). Appropriating the thought of Goethe, she finds that the emphasis shifts from the embrace of the One to an encounter with the mode of the Two (Assmann 1996: 100). This encounter is marked by awe and surprise, but also by the shrouding of each of the Two as if cloaked in eternal solitude. The question posed in this article is whether Assmann’s viewpoints may enhance a reading of a work from the South African art music repertoire, Hans Huyssen’s Ciacona & Tshikona (2007). Engaging with a broader selection of viewpoints on cultural translation, it is asked whether Assmann’s (1996: 99) notion of otherness is a productive context for mediating a meaningful encounter between cultures and whether, as such, it is relevant to an interpretation of Huyssen’s work. A speculative interpretation of Huyssen’s Ciacona & Tshikona reveals that the work is suggestive of a complex heredity being translated into an ‘impure’ new South African contextuality.